2006
DOI: 10.1128/aac.00625-06
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Treatment with Lopinavir-Ritonavir Induces a Reduction in Peripheral Adipose Depots in Mice

Abstract: Highly active antiretroviral therapy (HAART) of human immunodeficiency virus-infected patients is associated with adverse effects, such as lipodystrophy and hyperlipidemia. The lipodystrophic syndrome is characterized by a peripheral lipoatrophy and/or fat accumulation in the abdomen and neck. In order to get insights into the physiopathological mechanisms underlying this syndrome, we treated mice with protease inhibitors (PIs) over a long period of time. Although atazanavir-treated mice presented the same cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
(36 reference statements)
10
19
0
Order By: Relevance
“…For our study, there was a trend that showed PI treatment attenuated retroperitoneal fat pad mass compared to the other groups. This correlates with results from others who found significantly reduced retroperitoneal fat pad mass in mice treated with Ritonavir/Lopinavir [36,37]. It has been suggested that this may be linked to PI-mediated lowering of dietary intake in rodents [36,37], although this would need to be assessed in our model to determine whether indeed the case.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For our study, there was a trend that showed PI treatment attenuated retroperitoneal fat pad mass compared to the other groups. This correlates with results from others who found significantly reduced retroperitoneal fat pad mass in mice treated with Ritonavir/Lopinavir [36,37]. It has been suggested that this may be linked to PI-mediated lowering of dietary intake in rodents [36,37], although this would need to be assessed in our model to determine whether indeed the case.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were obtained following PI treatment of mice [36,37] and also within the clinical setting, e.g. the Study of Fat Redistribution and Metabolic Change in HIV Infection (FRAM) demonstrated lipoatrophy in HIV-infected men [38].…”
Section: Discussionsupporting
confidence: 70%
“…Murine clearance of LPV/RTV was substantial as little if any LPV could be detected in the mouse serum 8-h post-administration. 37 This prompted us to administer the drugs twice daily, with a minimum interval of 8 h. The LPV/RTV dosage had to be in the range of prescriptions established for humans and appropriate for a long-term treatment of mice. The chosen LPV dose was thus below that recapitulating the drug impregnation similar to the pattern observed in humans 37 (i.e., causing unwanted secondary effects).…”
Section: Resultsmentioning
confidence: 99%
“…We propose that inhibition of adipose glucose uptake by protease inhibitors is an early and important factor predisposing patients to lipoatrophy as well as peripheral insulin resistance. Clearly, additional factors are required for lipoatrophy to develop; especially important among these factors is treatment with NRTIs (Buffet et al 2005; Mallon et al 2003), but the direct association of PIs with white adipose tissue loss has been confirmed both clinically (Dube et al 2005; Heath et al 2002) and preclinically in the mouse (Prot et al 2006). …”
Section: Pis and Glucose Transportmentioning
confidence: 99%